2005
DOI: 10.1194/jlr.m500003-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin promotes preferential periportal upregulation of VLDL secretion in the rat liver

Abstract: Zonation affects liver parenchymal cell function and metabolism as well as nonparenchymal cell activation, but whether VLDL production is zonated has yet to be elucidated. Infection induces enhanced VLDL secretion by the liver. Ex vivo studies were undertaken to examine the liver heterogeneity for VLDL formation and secretion and their in vivo response to endotoxin. Highly pure periportal (PP) and perivenous (PV) hepatocytes were isolated from fasted lipopolysaccharide-treated, fasted, and fed rats. They were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 59 publications
4
40
0
Order By: Relevance
“…Rat and mouse hepatocytes were isolated by perfusion with collagenase as previously described (2) and, when necessary, they were incubated at 37°C and 5% CO 2 during 4 h. Plasma insulin levels range from 25 to 30 mU/l in Sprague-Dawley rats (21,25), from 17 to 22 mU/l in LZ rats, and from 70 to 110 mU/l in OZ rats (9). Plasma insulin levels range from 18 to 30 mU/l in C57BL/6J (23,29) mice and increase at least 5 times in ob/ob mice and in insulin-resistant-induced C57BL/6J mice (23,29).…”
Section: Methodsmentioning
confidence: 99%
“…Rat and mouse hepatocytes were isolated by perfusion with collagenase as previously described (2) and, when necessary, they were incubated at 37°C and 5% CO 2 during 4 h. Plasma insulin levels range from 25 to 30 mU/l in Sprague-Dawley rats (21,25), from 17 to 22 mU/l in LZ rats, and from 70 to 110 mU/l in OZ rats (9). Plasma insulin levels range from 18 to 30 mU/l in C57BL/6J (23,29) mice and increase at least 5 times in ob/ob mice and in insulin-resistant-induced C57BL/6J mice (23,29).…”
Section: Methodsmentioning
confidence: 99%
“…After 2 h, blood was collected and VLDLs (d < 1.006 g/ml) were isolated and characterized ( 23 ). The VLDL-TG and VLDL-apoB post-Triton accumulation in the serum serves as a measure of VLDL production rate.…”
Section: Determination Of Hepatic Vldl Productionmentioning
confidence: 99%
“…Rat hepatocytes were isolated as previously described ( 23 ) and used immediately for transcriptomics or functional studies. The hepatocyte suspensions had >80% viability and were >99% nonparenchymal cell free.…”
Section: Isolation Of Hepatocytes and Cellular Rnamentioning
confidence: 99%
“…The distribution of these cells may contribute to zonation of VLDL assembly, as in endotoxin-treated rats the increase in VLDL secretion occurs in periportal hepatocytes and is accompanied by higher apoB and MTP levels. 58 During fasting, the secretion of apoB was found to be decreased 58 and this was more pronounced in periportal hepatocytes, but the synthesis of lipids dominated perivenously. Another study 59 also showed that the zonation of oxidation of fatty acids is altered depending on the physiological status of the animal and that AMP activated protein kinase distribution, which is greater in the perivenous region, may also contribute 60 to the metabolic heterogeneity observed.…”
Section: Discussionmentioning
confidence: 97%